The Randomized Olmesartan and Diabetes Microalbuminuria Prevention (ROADMAP) observational follow‐up study: benefits of RAS blockade with olmesartan treatment are sustained after study discontinuation - Menne, Jan; Ritz, Eberhard; Ruilope, Luis M.; Chatzikyrkou, Christos; Viberti, Giancarlo; Haller, Hermann (Journal of the American Heart Association, 2014)
The Randomized Olmesartan and Diabetes Microalbuminuria Prevention (ROADMAP) study showed that 40 mg Olmesartan medoxomil (OM) versus placebo delayed microalbuminuria onset in patients with type 2 diabetes and normoalbuminuria.
Gesehen am 22.09.2020